Studi Identifikasi Faktor-faktor yang Mempengaruhi Motivasi Kerja Karyawan Koperasi Unit Desa Beringin Jaya I - Rangkuti, Afrizal; Yunita, Yunita (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2024)
This research aims to describe the study of factors that influence the work motivation of Beringin Jaya I Village Unit Cooperative Employees. This research method uses a descriptive quantitative approach, which emphasizes numerical data analysis using statistical methods. This research is non-experimental in nature. The research population consists of 51 employees of KUD Makmur Jaya in Beringin Jaya Village. The sample was determined using sampling techniques. Data was collected through an instrument in the form of a psychological scale using a Likert scale. The research results show that theories such as those put forward by Hasibuan, Mangkunegara, and Maslow emphasize that physical needs, security, social needs, self-esteem, and self-actualization play a crucial role in motivation. External factors such as leadership and work environment, as well as internal factors such as personal maturity and job satisfaction, also play an important role. The need for security is the most dominant factor in influencing work motivation, contributing 81.70%, while the need for self-actualization has the smallest contribution at 42.50%.